SISTEM TEMU KEMBALI INFORMASI METODE VSM (ABSTRAKSI SKRIPSI FTI UNISBANK) (Information Technology and Telematics, 2015)
Abstract Search engine is used by users to find information according to user needs. Searching uses search engines have different results because of the algorithms used by every search engine is different. Researching uses the Vector Space Model (VSM) was being made to provide search results by the number of documents drawn slightly (low recall) but high accuracy (high precision). The purpose of the design of information retrieval with VSM method is to allowing users to search for abstraction thesis FTI quickly and accurately. VSM method gives a different similarity values, the document with the highest similarity value is placed at the very top of the search results. This study through the process of Tokenization, disposal of existing stopword using stopword Tala, stemming process with Nazief algorithm Adriani, tf-idf weighting, the vector length calculation, and document similarity calculation. Keywords : Search Engine, Information Retrieval, Vector Sapace Model